Employees' perceptions as 'recipients' of change: a case study - Buoy, Lynette (Curtin University, 2002)
This research investigated employees' perceptions as 'recipients' of change. It did so by seeking to understand and represent their views regarding what influences effective change processes. The significance of this research was the focus on employee perceptions and not those of management. It was research conducted at a grass-roots level seeking to provide a voice for those least often heard or asked. The research was conducted using participants from two case study organisations in the local government sector of Western Australia employing approximately 200 staff each. Both organisations were metropolitan and had been experiencing change within their organisations for some time. Within this research it is recognised that the phenomenon of organisational change is by no means new. Since the early 1970s literature has emerged proposing that our world and the world of work, both internally and externally, are about to change. Management books and the history of management and organisational life have been filled for years with issues relating to change. These include changing management practices, new techniques for achieving change and dealing with threats of what nonchange may bring. As the research was seeking to interpret respondents' meaning relating to the phenomenon of organisational change, it was not concerned with quantification, but with understanding the phenomenon from the viewpoint of those experiencing the change. This research was based on the belief that human behaviour, unlike that of physical objects, cannot be understood without reference to the meanings and purposes attached by the human actors to their activities. The ontological assumption of a socially constructed reality underpinned this study. The realities experienced were those as interpreted by employees. The epistemological assumption was that of interpretivism.The realities experienced by respondents were subjective and, accordingly, the research's findings were literally created as the investigation proceeded. The methodological assumption was of a qualitative framework for understanding how change impacts on employees. Both the researcher and the employees under investigation therefore interacted in the process of meaning construction and clarification. The constructivist paradigm was therefore adopted as it emphasises a qualitative methodological approach. It was supported by theories of symbolic interactionism and phenomenology, which focus on the interpretation of the meaning of the employees' experiences within the phenomenon of organisational change. Grounded theory principles were used within the constructivist paradigm to provide a framework for ensuring that data analysis remained interpretative and that all emergent categories earned their place through the practices of constant comparison, not the preconceptions of the researcher. To further enhance this method, a triangulated approach to data sources and data collection methods for analysis included documentation, change manager interviews, and the primary sources of focus group interviews and individual in-depth interviews with employees. The findings are represented in a model identifying strategic efficiencies, organisational unity, skills and capabilities, humanistic application and relationship maintenance as the major factors as perceived by employees as influencing effective change. It presents both the what and the how of change as perceived by employees; i.e. what needs to be done and how.The model presented within this research is recognised as a tentative model dependent on further investigation and study. It provides a useful perception of what employees believe would create effective organisational change, and it demands close and careful consideration by strategists and practitioners. The model is unique in its structure and representative in regard to its information source.